Zinc in Keratinocytes and Langerhans Cells: Relevance to the Epidermal Homeostasis - Youichi Ogawa; Manao Kinoshita; Shinji Shimada; Tatsuyoshi Kawamura (Journal of Immunology Research)
In the skin, the epidermis is continuously exposed to various kinds of external substances and stimuli. Therefore, epidermal barriers are crucial for providing protection, safeguarding health, and regulating water balance by maintaining skin homeostasis. Disruption of the epidermal barrier allows external substances and stimuli to invade or stimulate the epidermal cells, leading to the elicitation of skin inflammation. The major components of the epidermal barrier are the stratum corneum (SC) and tight junctions (TJs). The presence of zinc in the epidermis promotes epidermal homeostasis; hence, this study reviewed the role of zinc in the formation and function of the SC and TJs. Langerhans cells (LCs) are one of the antigen-presenting cells found in the epidermis. They form TJs with adjacent keratinocytes (KCs), capture external antigens, and induce antigen-specific immune reactions. Thus, the function of zinc in LCs was examined in this review. We also summarized the general knowledge of zinc and zinc transporters in the epidermis with updated findings.